Commentary: Immediate Effect of Digital Game Use and Verbal Encouragement on Lower Limb Activity and Psychological Enjoyment During Motor Task in Children with Motor Disorders. - Sah, Ahana; Kumar, Amit (Physical & Occupational Therapy in Pediatrics, 2026)
The article focuses on a study by Asano et al. examining the use of digital game-based activities combined with verbal encouragement to improve motor engagement and enjoyment in children with motor disorders. The study employs a within-subject design to assess both objective lower limb activity and subjective enjoyment, contributing to pediatric neurorehabilitation research that integrates psychological and physical aspects. Methodological considerations include the fixed sequence of conditions without randomization, the lack of a verbal-encouragement-only condition, and limitations in sensor placement and outcome measurement tools. The authors suggest that future research with larger samples and standardized enjoyment assessments could strengthen the evidence for motivation-driven rehabilitation interventions in this population.